Finite element simulation of the woven geometry and mechanical behaviour of a 3D woven dry fabric under tensile and shear loading using the digital element method. (12th December 2016) - Daelemans, Lode; Faes, Jana; Allaoui, Samir; Hivet, Gilles; Dierick, Manuel; Van Hoorebeke, Luc; Van Paepegem, Wim
Abstract: This article provides a simulation methodology based on the concept of virtual fibres and digital elements which can be used to determine the mechanical behaviour of 3D woven fabrics. It takes the fibrous nature of the fabric into account by modelling a yarn as a bundle of virtual fibres. Whilst the digital element method has been typically used as a kinematic method to predict the geometrical behaviour of textile materials, its potential to also capture the mechanical behaviour of fabrics is still under research. Our methodology is able to predict the woven microstructure of a large unit cell 3D woven fabric based on simple input properties (weaving pattern, yarn stiffness) and to virtually asses its behaviour under tensile and shear loading. Hence, both the kinematic and mechanical behaviour of the fabric is taken into account. The main advantage of this methodology is that the simulations are able to predict the mechanical response of the fabric by considering the sub-yarn behaviour without the requirement of complex constitutive laws. Good agreement with experimental data was obtained, indicating the usability of this method to model the mechanical behaviour of a large unit cell 3D woven fabric.